2017
DOI: 10.1038/s41593-017-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the underlying components of food valuation in the human orbitofrontal cortex

Abstract: The valuation of food is a fundamental component of our decision-making. Yet, little is known about how value signals for food and other rewards are constructed by the brain. Utilizing a food-based decision task in human participants, we found that subjective values can be predicted from beliefs about constituent nutritive attributes of food: protein, fat, carbohydrate and vitamin content. Multivariate analyses on fMRI data demonstrated that while food value is represented in patterns of neural activity in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
158
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(210 citation statements)
references
References 48 publications
(70 reference statements)
26
158
4
1
Order By: Relevance
“…It is well known that striatum activity tracks subjective pleasantness induced by various stimuli such as faces and foods (e.g., [33,38]). However, it should also be noted that the ventromedial prefrontal cortex (vmPFC) is also known to be robustly related to subjective pleasantness (e.g., [38][39][40][41]), but we did not find any activation negatively related to social conflict in the vmPFC.…”
Section: Discussioncontrasting
confidence: 75%
“…It is well known that striatum activity tracks subjective pleasantness induced by various stimuli such as faces and foods (e.g., [33,38]). However, it should also be noted that the ventromedial prefrontal cortex (vmPFC) is also known to be robustly related to subjective pleasantness (e.g., [38][39][40][41]), but we did not find any activation negatively related to social conflict in the vmPFC.…”
Section: Discussioncontrasting
confidence: 75%
“…The reward system integrates across dimensions to generate abstract decision variables; that is, ones that are correlated with value (e.g. Barron et al, 2017; Blanchard et al, 2015; Fellows, 2006; Hayden, 2016; Hunt and Hayden, 2017; Raghuraman and Padoa-Schioppa, 2014; Strait et al, 2014; Suzuki et al, 2017). However, unlike the visual system, which has only one major input locus—the eyes—the reward system has many inputs.…”
Section: Untangling Information In Form Visionmentioning
confidence: 99%
“…() demonstrated that, specifically the lateral OFC represents nutritive valuation of a food (protein, fat, sodium, carbohydrate and overall energy value) and that this information is then integrated with information from the medial OFC to determine an overall subjective value of a food (willingness to pay) (Suzuki et al . ). Whether this relationship is affected in obesity warrants further investigation.…”
Section: Connectivity Of the Lateral Hypothalamusmentioning
confidence: 99%
“…Interestingly, increase in BOLD activity in the OFC in obese humans in response to food odours has been demonstrated to be associated with selfreported poor impulse control (Eiler et al 2014), suggesting this region may be implicated in the decision to consume palatable food despite known negative consequences. Recently, a study in healthy weight individuals by Suzuki et al (2017) demonstrated that, specifically the lateral OFC represents nutritive valuation of a food (protein, fat, sodium, carbohydrate and overall energy value) and that this information is then integrated with information from the medial OFC to determine an overall subjective value of a food (willingness to pay) (Suzuki et al 2017). Whether this relationship is affected in obesity warrants further investigation.…”
Section: Orbital Frontal Cortexmentioning
confidence: 99%